PURA SAMUAN TIGA : PERSPEKTIF MEDIA KOMUNIKASI HINDU - Wirta, I Wayan (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2020)
The number of sect (Hindu religious schools) that developed in Bali in the past was feared by various groups would lead to religious disharmony. The formulation of the problem of this research : 1) Why did Samuantiga Temple as a medium of Hindu communication, 2) How did Hindus Use Samuantiga Temple as a medium of communication, and 3) What were the implications of Samuantiga Temple as a medium of Hindu communication. The research objective was to obtain the factors that cause Samuantiga Temple as a Hindu communication media, understand the use of Samuantiga Temple as a Hindu communication media and to obtain the implications of Samuantiga Temple as a Hindu communication media. The theory used attribution, cybernetics, sadharanikaran model and dependency theory. Data collection techniques were observation, in-depth interviews, documentation and library research, while data analysis techniques were: data reduction, display and verification.The results of this dissertation study were as follows : 1) Samuantiga Temple as a Hindu communication media was caused by several factors, including : a) Theological factors namely knowledge and understanding of the divine aspects worshiped at Samuantiga Temple included the concept of worship of ?iva Buddha, ?iva ?iddhanta and Tri M?rti. b) Socio-ideological factors, namely human thought factors regarding the structure of the community supporting the Samuantiga Temple consisting of Bali Aga/Bali Mula and Bali Apanaga. c) The historical and political factors of the power of the Bedahulu kingdom government, in line with the evolution of the level of progress of human thought in understanding God, d) The geographical and strategic location of Samuantiga Temple, as the center or center of the island of Bali so that it was easily accessible from all directions, e) Factors cultural preservation, namely the efforts of Hindus to maintain and preserve the adhiluhung cultural heritage, as a center for the application of the concept of Tri M?rti worship in Bali. 2) The use of Samuantiga Temple as a medium of Hindu communication, including: the use of palinggih-palinggih, statues, pratima, site/pralingga Ida Bhatara as a medium of concentration of Hindus. The five gita is a complementary media stimulating the concentration of the mind in worship, while the offering/upakara serves as a medium for offerings and purification.3) The implications of Samuantiga Temple as a medium of Hindu communication, included : Implications of strengthening sraddha and devotional services in the form of the strengthening of the Hindu beliefs of the Samuantiga Temple pengempon; the implication of Samuantiga Temple as a center for spiritual education; the implications of regulating the family recruitment strategy, namely how to anticipate household needs in connection with the cost of work in Padudusan and the implications for the security of Pakraman/customary villages and the existence of KahyanganTiga in Bali.The findings of the research in Samuantiga Temple are : the Balinese version of the Hindu Communication Model, namely the process of delivering one's Vedic messages to others (Hindus) through the implementation of ceremonies yajña in the Balinese tradition, accompanied by bh?va and taste elements so that the sahridayata (common understanding) is achieved as the main goal to be achieved in the communication process, so that vertical harmonious relationships (parhyangan, palemahan) and horizontal (pawongan), was abstract, its communicantwas not limited to humans.